End-tidal carbon dioxide-guided extracorporeal cardiopulmonary resuscitation improves neurological prognosis in patients: a single-center retrospective cohort study - Xiaozu Liao; Chen Gu; Zhou Cheng; Kepeng Liu; Qing Yin; Binfei Li (Brazilian Journal of Anesthesiology)
Background: Extracorporeal Cardiopulmonary Resuscitation (ECPR) is an effective intervention for restoring adequate circulatory perfusion after cardiac arrest. Ensuring high-quality Cardiopulmonary Resuscitation (CPR) before initiating Extracorporeal Membrane Oxygenation (ECMO) is critical to mitigate tissue hypoxia and ischemia. This study aimed to evaluate the effect of End-Tidal Carbon Dioxide (ETCO2) Goal-Directed CPR (GDCPR) on neurological function before ECMO using a retrospective case-control analysis. Methods: The medical records of all patients who received ECPR treated at Zhongshan City People's Hospital were collected between January 2020 and March 2023. In this retrospective cohort study, the patients were divided into Conventional CPR (CCPR) and ETCO2-GDCPR groups based on whether ETCO2 was used as a guide for CPR. Results: A total of 71 patients were included, of whom 46 comprised the CCPR group and 25 comprised the GDCPR group. Approximately 37% of patients who received ECPR had good cerebral function at discharge, with a higher rate in the GDCPR group (52%) compared with the CCPR group (28%) (p = 0.047). Multivariate analysis showed that the Highest Interleukin-6 (H-IL6) levels after ECMO (Odds Ratio [OR = 1.001], 95% Confidence Interval [95% CI 1.000–1.003], p = 0.005) was a risk factor for neurological function at discharge. The other risk factors for poor prognosis in patients who received ECPR included pre-ECMO CPR protocols (OR = 10.74, 95% CI 1.90–60.48, p = 0.007) and IL6 levels after ECMO (OR = 1.002, 95% CI 1.001–1.003, p = 0.005). ECMO duration (OR = 0.83, 95% CI 0.74–0.94, p = 0.002) was identified as a protective factor. Patients with short ECMO duration have a poor prognosis. The area under the curve for ECMO duration was 0.86 (0.77–0.94, p < 0.01), while that for H-IL6 was 0.19 (0.09–0.29, p < 0.01). Conclusion: ETCO2-guided ECPR is associated with improved neurological prognosis and patient outcomes. Therefore, monitoring ETCO2 levels should be considered a crucial component of evaluating resuscitation efficacy during CPR.